Integrating Empiricism and Jean Piaget's Cognitive Theory to Foster Creativity in Dance Learning in Elementary Schools: A Systematic Literature Review - Wecya Sugevin; Sigit Wibowo (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
Dance learning in elementary schools plays an important role in fostering students' creativity through aesthetic and experiential activities. However, learning practices are still frequently dominated by teacher demonstrations and video-based instruction, limiting students' opportunities to explore their environment and construct creative experiences independently and actively. Previous studies have widely discussed experiential learning and Jean Piaget's cognitive theory separately, but studies integrating the empiricism paradigm with Piaget's cognitive perspective in elementary school dance learning remain limited. Therefore, this study aims to examine the relevance of the empiricism paradigm and Jean Piaget's cognitive theory in fostering creativity in elementary school dance education. This study employed a literature review method using a narrative review design. Data were collected from 52 scientific sources, including international journal articles, accredited national journals, conference proceedings, and relevant books, obtained from the Scopus, SINTA, and Google Scholar databases. The data were analyzed descriptively using the interactive analysis model of Miles and Huberman, including data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the empiricism paradigm emphasizes sensory experience, environmental interaction, and observation as the primary foundations for the development of creativity in dance learning. Meanwhile, Jean Piaget's cognitive theory holds that elementary school students at the concrete operational stage require contextual and direct learning experiences to actively construct knowledge. The study further reveals that both perspectives are conceptually interconnected through three major aspects: sensory experience, active learning, and environmental exploration, which collectively support students' creativity formation in dance learning. In practice, this study implies that teachers should design dance learning activities that prioritize direct interaction with the environment, student exploration, and experiential learning to create more meaningful, creativity-oriented learning processes in elementary schools.